(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Halal awareness is how knowledge about the process of slaughtering, food packaging and food hygiene in accordance with Islamic law. Halal awareness leads to an understanding of the urgency of halal certification where halal certification is a guarantee of security for sHalal awareness is how knowledge about the process of slaughtering, food packaging and food hygiene in accordance with Islamic law. Halal awareness leads to an understanding of the urgency of halal certification where halal certification is a guarantee of safety for a series of detailed inspection processes to obtain halal legality and become a parameter guaranteeing product safety for Muslim consumption. Halal awareness and understanding of halal certification that is still lacking in the Dayak Bidayuh community who are converts to Islam led the service team of the Master of Sharia Economics (MES) Study Program of the Pontianak State Islamic Institute (IAIN) to carry out service in Darul Falah Village, the majority of which are Dayak Bidayuh people. The purpose of this research is to find out how the awareness and understanding of the Dayak Bidayuh community about halal certification. The method used is in-depth interviews with the Dayak Bidayuh community in Tebedu, Sarawak. The results obtained were that the Dayak Bidayuh community who converted to Islam experienced changes in halal awareness and understanding of the urgency of halal certification. a series of detailed inspection processes in order to obtain halal legality and become a parameter guaranteeing product safety for Muslim consumption. Halal awareness and understanding of halal certification that is still lacking in the Dayak Bidayuh community who convert to Islam led the dedication team of the Master of Sharia Economics (MES) Study Program of the Pontianak State Islamic Institute (IAIN) to carry out community service in Darul Falah Village, the majority of which are Dayak Bidayuh people. The purpose of this research is to find out how the awareness and understanding of the Dayak Bidayuh community about halal certification. The method used is in-depth interviews with the Dayak Bidayuh community in Tebedu, Sarawak. The results obtained are that the Dayak Bidayuh community who converted to Islam experienced changes in halal awareness and understanding of the urgency of halal certification.